The exploration of the experiences of alienation in education for rural high school learners in the Eastern Cape province, South Africa - Moleko, Teboho Banele (Department of Sociology, 2025)
Rural high school learners - learners who attend schools in rural areas - face well-documented macro-level educational challenges: lack of access to social services, poor infrastructure and educational resources, pronounced disadvantage, and limited exposure to experienced teachers. Yet, very little is known about rural high school learners' experiences. Additionally, there is a dearth of information regarding rural high school learners' experiences from their perspectives. To remedy these knowledge gaps, the research was steered by the following questions, “How do rural high school learners in the Eastern Cape experience alienation in education?” “How is rurality framed in education policy, and how does this play a role in alienating rural learners in education?” This thesis used the theory of alienation in education as a guide to uncover the textured, in-depth, contextual experiences of rural learners in the Eastern Cape. More so, this thesis was conducted using qualitative research methodology. The study f